2013
DOI: 10.1097/mnm.0b013e32835ce5b5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a matched filter resolution recovery reconstruction algorithm for SPECT-CT imaging

Abstract: The use of such an algorithm results in images characterized by increased spatial resolution and reduced noise. However, small sources of the order of 2-3 cm can be significantly overenhanced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…O’Mahoney et al evaluated a specific OSEM RR (Astonish) modality designed for the Philips SPECT/CT for the conventional OSEM reconstruction algorithm (12) . This study was conducted with a Jaszczak phantom.…”
Section: Discussionmentioning
confidence: 99%
“…O’Mahoney et al evaluated a specific OSEM RR (Astonish) modality designed for the Philips SPECT/CT for the conventional OSEM reconstruction algorithm (12) . This study was conducted with a Jaszczak phantom.…”
Section: Discussionmentioning
confidence: 99%
“…This problem can be compensated by the OSEM algorithm cooperated with RR. O'Mahoney et al (24) evaluated that RR could not only signi cantly enhance spatial resolution and reduce PVE, but also suppress noise and provide better contrast. In myocardial perfusion SPECT/CT, OSEM combined with RR could correct myocardial perfusion distribution and compensate for the depth-dependent blurring (25).In our study, RR highly enhanced spatial resolution, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The most widely used approach for enhancing the spatial resolution is to include the point spread function (PSF) of the imaging system in the system matrix used in the forward- and back-projection steps of the iterative reconstruction, ie, including the PSF within the reconstruction framework, also known as resolution recovery. Although resolution recovery leads to substantial improvement in activity quantification, especially in small structures, a disadvantage is the appearance of ringing artifacts in the image (O’Mahoney and Murray, 2013; Rahmim et al , 2013).…”
Section: Quantification Of Activity In Source Regions For Dosimetrymentioning
confidence: 99%